Complicating Access: Digital Inequality and Adult Learning in a Public Access Computing Space - Smythe, Suzanne; Breshears, Sherry (Canadian Journal for the Study of Adult Education, 2017)
Abstract Access is often defined in digital inclusion policy as the potential, if not the means, to access an Internet connection. This simple or ‘laissez-faire’ approach to digital access excludes many of the adults who are also the constituents of adult literacy education programs, suggesting the need for adult educators to attend closely to the entanglements of digital equity and adult learning. Combining methods of critical policy analysis with participant observation of adults’ experiences of digital access and learning in a public setting, the study identifies tensions between public sites for computing learning and the privatization of access, between ‘basic skills’ and critical pedagogies of production, and between the ‘model users’ for whom digital policies and the Internet are designed and the actual experiences of those who are on the margins of access. These trouble spots provoke new challenges and possibilities for a reinvigoration of public computing as new sites for adult learning.